A computational model for hybrid nanofluid flow on a rotating surface in the existence of convective condition. (August 2021) - Hussain, Azad; Alshbool, Mohammed Hamed; Abdussattar, Aishah; Rehman, Aysha; Ahmad, Hijaz; Nofal, Taher A.; Khan, M. Riaz
Abstract: The current work aims to study heat transfer properties within the flow. A newly developed idea regarding hybrid nanofluid is utilized to obtain the desired outcomes. This study focused on hybrid base nano liquid flow past an exponentially stretching rotating surface in the presence of the convective condition. Ethylene glycol-water (50%–50%) mixture is taken as base fluid. Thermophysical properties are discussed. The probe of emerging parameters indicates that hybrid base nanofluid gives a preferable rating as compared to nanofluid. Appropriate choice of composition plays a vital role. Physical characteristics of essential parameters such as Prandtl number, convective parameter, stretching ratio, rotation parameter, and temperature exponent are evaluated. Graphical depiction reveals that the velocity curve decline by increasing rotation parameter for CuO-hybrid base fluid and TiO2 hybrid base fluid. By expanding the values of the stretching ratio the velocity profile p ′ ( η ) is decreasing while the velocity curve q ′ ( η ) increased for CuO as well as TiO2 hybrid base fluid. Concentration boundary layer thickness growing by enlarging rotation parameters for both types of nanofluid. Moreover, the influence of various parameters on skin friction factor and Nusselt numbers are also evaluated.